Supervisi Akademik Kepala Sekolah terhadap Kompetensi Pedagogik Guru di SMPIT Qurrata A’yun Batusangkar - Sri Aisyah Amini; Demina Demina; Muhammad Fazis; Asmendri Asmendri; Yanti Elvita (Jurnal Manajemen Pendidikan Islam (MANAPI), 2022)
The purpose of this study is to describe and analyze academic supervision which consists of (1) planning the principal's academic supervision on the pedagogic competence of teachers (2) the implementation of the principal's academic supervision on the teacher's pedagogic competence (3) evaluating the results of the principal's academic supervision on pedagogic competence. teachers (4) follow-up of the principal's academic supervision on the teacher's pedagogic competence. This research is a qualitative research with a phenomenological approach. Data was collected through interviews, and documentation. Sources of data, namely primary data and secondary data obtained from three objects, namely the head of SMPIT Qurrata A'yun Batusangkar and teachers, places held at SMPIT Qurrata A'yun Batusangkar, and papers containing documents about the results of academic supervision. The results showed, (1) planning for academic supervision of teacher pedagogical competence has been carried out well (2) Implementation of academic supervision on teacher pedagogic competence, namely (a) individual supervision techniques (b) group supervision techniques. (3) Evaluation of the results of academic supervision in the form of measuring and assessing the realization of the planned program and its impact. (4) Following up on academic supervision to improve the pedagogic competence of classroom teachers in the form of giving awards and training to teacher competencies.